2023
DOI: 10.1021/acscatal.3c00248
|View full text |Cite
|
Sign up to set email alerts
|

Surface Oxygen Vacancy and Hydride Species on Ceria Are Detrimental to Acetylene Semihydrogenation Reaction

Abstract: Reactivity of OH and hydride species in oxide-catalyzed hydrogenation reactions has attracted great interest. Herein, we report a combined in situ spectroscopic characterization and density functional theory (DFT) calculation study of ceria-catalyzed acetylene semihydrogenation reaction. The ceria surface is fully hydroxylated during the adopted reaction condition. C2H2 adsorbs molecularly on the stoichiometric CeO2 surface and hydrogenates with OH groups selectively to produce C2H4. Semihydrogenation of C2H2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Although H-H heterolytic splitting at SA-O sites is more kinetically favored than at the Ti-O site, it is thermodynamically unfavored, except for Ni. Given that protons and hydrides exhibit distinct hydrogenation activity, as well as the role of surface H species in controlling the kinetics, our results offer insights into the optimal single atom catalyst for hydrogenation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Although H-H heterolytic splitting at SA-O sites is more kinetically favored than at the Ti-O site, it is thermodynamically unfavored, except for Ni. Given that protons and hydrides exhibit distinct hydrogenation activity, as well as the role of surface H species in controlling the kinetics, our results offer insights into the optimal single atom catalyst for hydrogenation.…”
Section: Resultsmentioning
confidence: 91%
“…Song et al found that the metal center binding to hydrides bears an electron-deficient state and drives propane dehydrogenation by lowering the dehydrogenation barrier . Wu et al studied the acetylene semihydrogenation over ceria and their results demonstrate the detrimental role of surface vacancy (V O ) and hydrides in the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, only if the ceria surface possessed sufficient but not excessive amount of O v and Ce–H at the same time, the propyne production reached a maximum, showing a synergistic role of the O v sites and Ce–H species on ceria catalysts. Note that this is consistent with the recent study based on ceria powder, which proposed that excessive O v and Ce–H are detrimental to selective hydrogenation of acetylene …”
Section: Resultsmentioning
confidence: 99%
“…The presence of surface hydride species in weakening the adsorption of reaction intermediates, facilitating the hydrogenation reaction and preventing coke formation could be further corroborated by DFT calculation results (Figure S7, Table S3). It needs to be mentioned that the surface models used here were built on the basis of the experimental characterizations in the current work, and they are different from those adopted in a recent work done by some of the authors . Hydride species can inhibit the dissociative adsorption of propyne.…”
Section: Resultsmentioning
confidence: 99%
“…These results clearly suggested that the Cu substrate may help maintain the Ce 3+ states and play a key role in the hydride formation in CeO x /Cu composites, which can be further supported by the significantly larger loss of Bader charges of Cu atoms during this process (see Figure S7). Such a unique electronic transfer process for the hydride species formation on the CeO x /Cu composites indicated that it cannot be detected by monitoring the oxidation state change from Ce­(III) to Ce­(IV) only, , and this is closely related to the electronic oxide–metal strong interaction (EOMSI) concept recently postulated by Huang et al. , that such interactions can maintain the electronic structures of the oxide adlayers with a low oxidation state under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%